2020
DOI: 10.1001/jamacardio.2020.3377
|View full text |Cite
|
Sign up to set email alerts
|

Association of Culprit Lesion Location With Outcomes of Culprit-Lesion-Only vs Immediate Multivessel Percutaneous Coronary Intervention in Cardiogenic Shock

Abstract: with a culprit lesion located in the left main or proximal left anterior descending artery compared with other coronary segments is associated with more myocardium at risk and worse clinical outcomes.OBJECTIVE To evaluate the association of culprit lesion location with outcomes of culprit-lesion-only percutaneous coronary intervention with optional staged revascularization vs immediate multivessel percutaneous coronary intervention in patients with multivessel disease, myocardial infarction, and cardiogenic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…CardShock substudy 13 also reported no difference between infarct-related arteries for mortality. In contrast to these two studies, a post hoc analysis 12 reported that patients with left main and proximal left anterior descending artery as a culprit lesion had worse mortality rates compared to those with the others and the right coronary artery was more frequent in the survivor group.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…CardShock substudy 13 also reported no difference between infarct-related arteries for mortality. In contrast to these two studies, a post hoc analysis 12 reported that patients with left main and proximal left anterior descending artery as a culprit lesion had worse mortality rates compared to those with the others and the right coronary artery was more frequent in the survivor group.…”
Section: Discussionmentioning
confidence: 77%
“…11 Prognostic role of culprit lesion was thought to be determined only by location, in previous studies. 12 −14 We postulated that the prognostic value of culprit-lesion SS (cul-SS) might be different from SS and nonculprit SS (ncul-SS) in patients with CS-STEMI. This study aimed to evaluate the predictive utility of cul-SS and other predictors for in-hospital mortality among patients with CS-STEMI.…”
mentioning
confidence: 99%
“…Although the rates of rehospitalization for heart failure and repeat revascularization were higher in the culprit lesion-only revascularization group, mortality did not differ significantly between the two groups at one year. A post-hoc analysis of the CULPRIT-SHOCK trial showed that culprit lesion PCI vs. multivessel PCI resulted in a significantly lower risk of death and kidney replacement therapy at 30 days (45.6% vs. 63.5%; p = 0.007) and of mortality at 1 year (50% vs. 69.6%; p = 0.003) only in patients with a culprit lesion of the left main or proximal left anterior descending artery [ 54 ]. It is important to note the limitations of the trial in which only 28% of patients received a mechanical circulatory support device, including that 12% of the total cohort were supported with the transvalvular axial flow device Impella (Abiomed, Danvers, MA, USA).…”
Section: Complete Revascularization In Cardiogenic Shockmentioning
confidence: 99%
“…1) [61]. Moreover, no clear evidence exists with regards to the prognostic value of distal versus proximal culprit location [56,62]. However, in the interpretation of these results, direct comparison should be done with caution as patient characteristics and management varies between studies.…”
Section: The Impact Of the Coronary Culprit Lesionmentioning
confidence: 99%